Mobile phone innovation and doing business in Sub-Saharan Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
This study assesses how knowledge diffusion modulates the effect of the mobile phone on entrepreneurship or doing business in Sub-Saharan Africa. The empirical evidence is based on Generalised Method of Moments in which mobile phones are interacted with three knowledge diffusion variables, namely: education, internet penetration and scientific output. Ten variables of entrepreneurship are used. The following three main findings are established. First, the net effects from interacting mobile phones with the internet and scientific publications are negative whereas the corresponding net impact from the interaction between mobile phones and education is positive on the cost of doing business. Second, the mobile phone interacts with education (the internet) to have a positive (negative) net effect on the time needed to construct a warehouse whereas, the corresponding interaction with the internet yields a net negative effect on the time to enforce a contract. Third, there is a positive net effect from the interaction of mobile phones with education on the time to start a business. Given the construction of the education variable, the positive net effects from education are consistent with corresponding negative net effects from the other knowledge diffusion variables.
Keywords: L59; L98; O10; O30; O55; 330; Entrepreneurship; the Mobile Phone; Knowledge Diffusion; Sub-Saharan Africa